2008
DOI: 10.1021/nl072991l
|View full text |Cite
|
Sign up to set email alerts
|

DNA Sensing by Silicon Nanowire: Charge Layer Distance Dependence

Abstract: To provide a comprehensive understanding of the field effect in silicon nanowire (SiNW) sensors, we take a systematic approach to fine tune the distance of a charge layer by controlling the hybridization sites of DNA to the SiNW preimmobilized with peptide nucleic acid (PNA) capture probes. Six target DNAs of the same length, but differentiated successively by three bases in the complementary segment, are hybridized to the PNA. Fluorescent images show that the hybridization occurs exclusively on the SiNW surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
193
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 266 publications
(198 citation statements)
references
References 23 publications
4
193
0
1
Order By: Relevance
“…To investigate the field effect in SiNW sensor, we first designed an approach to vary the distance of the charge layer away from the sensing surface by tuning the binding sites of DNA-PNA hybridization while maintaining charges constant (Zhang et al 2008). The recorded results showed that the detection sensitivity was distance dependent that agreed well with the theoretical analysis.…”
Section: Pna-dna Hybridizationssupporting
confidence: 57%
“…To investigate the field effect in SiNW sensor, we first designed an approach to vary the distance of the charge layer away from the sensing surface by tuning the binding sites of DNA-PNA hybridization while maintaining charges constant (Zhang et al 2008). The recorded results showed that the detection sensitivity was distance dependent that agreed well with the theoretical analysis.…”
Section: Pna-dna Hybridizationssupporting
confidence: 57%
“…I). [74][75][76][77]80] At the end of this review, we will discuss in details that recent progresses on operating GFETs at high frequencies suggested that Debye screening can be overcome: [46] 1.…”
Section: Debye Screeningmentioning
confidence: 99%
“…Possible routes to circumvent the Debye screening effect include short antibody design, porous polymer incorporation, and ex situ measurement in low ionic strength buffers (see Section 2.5). [74][75][76][77]80] These approaches, however, also impose limitations on the biodetection and it is highly desirable to develop a straightforward methods to overcome the Debye screening: [46] 1. without any special design or engineering of the receptor molecules and the sensor environments, and 2. in physiological conditions to facilitate in-situ, real-time biosensing. Theoretically, improved sensitivity is expected at high frequencies using a measuring strategy that overcomes the ionic screening effect.…”
Section: Overcoming the Debye Length Limitations With Radio-frequencymentioning
confidence: 99%
“…In addition to CNTs, Silicon nanowires (SiNWs) have attracted a great attention in recent years because of their excellent physical and chemical properties, and their potential applications in many areas including biosensor, 65,66 electronic device, 67,68 and solar photovoltaics. 69,70 SiNWs are appealing choice due to their ideal interface compatibility with conventional Si-based devices.…”
Section: A 1d Nanostructuresmentioning
confidence: 99%